ENERGY AWARE GPSR ROUTING PROTOCOL IN A WIRELESS SENSOR NETWORK - Nouh, Sayed; Geta, Zewdu (Zede Journal of Ethiopian Engineers and Architects, 2023)
Energy is the scarce resource in wireless sensor networks (WSNs), and it determines the lifetime of WSNs. For this reason, WSN algorithms and routing protocols should be selected in a manner which fulfills these energy requirements. This paper presents a solution to increase the lifetime of WSNs by decreasing their energy consumption. The proposed solution is based on incorporating energy information into Greedy Perimeter Stateless Routing (GPSR) Protocol. The proposed solution performs better in energy consumption, network lifetime and packet delivery ratio, with a performance gain of Network Lifetime 45.9% - 78.69%. However, the performance is comparatively low in average delay because of computational complexity. Key Words: Wireless Sensor Networks, GPSR protocol, Geographical routing protocol, ` Energy aware routing protocol,